Imagem-corpo-Frida: fronteiras híbridas da Performance na Arte Contemporânea a partir de uma perspectiva autobiográfica - Castro, Crystian Danny da Silva (2021)
This work researches the possibilities of creation in Art Performance from images of the mexican painter Frida Kahlo (1907-1954), emphasizing the crossings with life / autobiographical experiences as the guiding axis. Thereby, the methodological approach of Bricolage was used, articulating its polysemic feature and its creative-investigativeinterpretative network as a way of crossing different conceptual and artistic perspectives. Therefore, the present research aims to discuss, with the creation as basis, the incidence of Frida Kahlo’s images in contemporary culture, in the subjectivity production and multiples ways of artistic creation; the images’ power, based on Visual Culture studies; and the different ways to understand the field of Art Performance. To do that along the investigative path performances entitled Vinte e Quatro Outonos, O Vale and the video performance Gen(te)rra were made, it stimulate the performance conception using three biases: self art, art as way of existence and art as boundary. Different context/concepts are analyzed through creative processes, aiming inter-act with the trait of crossing art and life and the personal-political plot which are present both in the creation of Frida Kahlo and principles of Contemporary Art, in order to think of Art Performance as a borderline artistic expression, hybrid and plural that moves different bodies and their autobiographies as ways of being and creating in art.